Radial basis function network applied to the linearization of a voltage controlled oscillator - Lucks, Marcio B. [UNESP]; Oki, Nobuo [UNESP] (Association for Computing Machinery (ACM), 2007)
An analog circuit that implements a radial basis function network is presented. The proposed circuit allows the adjustment of all shape parameters of the radial functions, i.e., amplitude, center and width. The implemented network was applied to the linearization of a nonlinear circuit, a voltage controlled oscillator (VCO). This application can be classified as an open-loop control in which the network plays the role of the controller. Experimental results have proved the linearization capability of the proposed circuit. Its performance can be improved by using a network with more basis functions. Copyright 2007 ACM.
Keywords: Artificial neural networks; Linearization; Operational transconductance amplifier; Radial basis function; VCO; Radial functions; Amplifiers (electronic); Analog circuits; Parameter estimation; Radial basis function networks; Variable frequency oscillators